Losartan prevents acquired epilepsy via TGF‐β signaling suppression. Issue 6 (28th May 2014) - Bar‐Klein, Guy; Cacheaux, Luisa P.; Kamintsky, Lyn; Prager, Ofer; Weissberg, Itai; Schoknecht, Karl; Cheng, Paul; Kim, Soo Young; Wood, Lydia; Heinemann, Uwe; Kaufer, Daniela; Friedman, Alon
<x xml:space="preserve">Abstract</x> Objective Acquired epilepsy is frequently associated with structural lesions after trauma, stroke, and infections. Although seizures are often difficult to treat, there is no clinically applicable strategy to prevent the development of epilepsy in patients at risk. We have recently shown that vascular injury is associated with activation of albumin‐mediated transforming growth factor β (TGF‐β) signaling, and followed by local inflammatory response and epileptiform activity ex vivo. Here we investigated albumin‐mediated TGF‐β signaling and tested the efficacy of blocking the TGF‐β pathway in preventing epilepsy. Methods We addressed the role of TGF‐β signaling in epileptogenesis in 2 different rat models of vascular injury, combining in vitro and in vivo biochemical assays, gene expression, and magnetic resonance and direct optical imaging for blood–brain barrier permeability and vascular reactivity. Long‐term electrocorticographic recordings were acquired in freely behaving animals. Results We demonstrate that serum‐derived albumin preferentially induces activation of the activin receptor‐like kinase 5 pathway of TGF‐β receptor I in astrocytes. We further show that the angiotensin II type 1 receptor antagonist, losartan, previously identified as a blocker of peripheral TGF‐β signaling, effectively blocks albumin‐induced TGF‐β activation in the brain. Most importantly, losartan prevents the development of delayed recurrent spontaneous seizures, an effect that persists weeks after drug withdrawal. Interpretation TGF‐β signaling, activated in astrocytes by serum‐derived albumin, is involved in epileptogenesis. We propose losartan, a drug approved by the US Food and Drug Administration, as an efficient antiepileptogenic therapy for epilepsy associated with vascular injury. Ann Neurol 2014;75:864–875